El legado de Ernesto Laclau a las ciencias sociales y humanas (2014)
This paper examines some central axis from theoretical and political legacy of Laclau´s work to Social Sciences and Humanities. In this context, highlights some fundamental contributions from his political and social theory to the development of post-foundational political thought and socio-political and critical analysis.